Transvaginal ultrasonography is the diagnostic method for evaluation of abnormal uterine bleeding (Journal of Shaheed Suhrawardy Medical College, 2012)
Objective: The objective of this study is to assess the utility of transvaginal ultrasonography in patients presenting abnormal uterine bleeding Materials and methods: Between July 2000 to December 2000, 50 patients underwent transvaginal sonography (TVS) for abnormal uterine bleeding. All patients had transvaginal sonography before histopathology. On TVS, the sonographic appearance of the endometrium was classified according to the following parameters: normal or abnormal thickness, homogeneous or heterogeneous echogenicity, bulbous contour, discontinuous, or obscured. A comparison was performed between TVS with histopathology. Results: The most common causes for the abnormal uterine bleeding were leiomyoma in TVS (42.0%). Other causes were dysfunctional uterine bleeding (28.0%). adenomyosis (6.0%), endometrial polyp (4.0%), thin atrophic endometrium (8.0%), endometrial hyperplasia (8.0%), and endometrial carcinoma (4.0%). After histopathologic evaluation 40.0% patients had leiomyoma, 24.0% DUB, 10.0% adenomyosis, 8.0% endometrial polyp, 8.0% thin atrophic endometrium, 6.0% endometrial carcinoma and 4.0% endometrial hyperplasia. Comparing the TVS with histopathologic findings, TVS had a sensitivity of 94.3%, specificity of 80.0%. accuracy of 90.0%, PPV of 91.6% and NPV of 85.7%. Conclusion: TVS is an easy, safe, rapid and tolerable procedure. It has an excellent diagnostic accuracy in the diagnosis of uterine pathology responsible for abnormal uterine bleeding. Abbreviation: TVS transvaginal sonography; AUB abnormal uterine bleeding; DUB dysfunctional uterine bleeding, PPV positive predictive value, NPV Negative predictive value. DOI: http://dx.doi.org/10.3329/jssmc.v1i1.12168 Journal of Shaheed Suhrawardy Medical College Vol.1, No.1, December 2009 p.11-13